Taguchi method for the determination of optimised sintering parameters of titanium alloy foams - Ahmad, S.; Muhamad, N.; Muchtar, A.; Sahari, J.; Jamaludin, Khairur Rijal; Ibrahim, Mohd. Halim Irwan; Mohamad Nor, N. H. (2009)
Sintering is a key step in the preparation of metal foams. The present work focuses on the sintering effects on the properties of titanium foam prepared using the slurry technique. Sintering affects the density as well as the mechanical properties of the sintered parts. To achieve a high density of the titanium alloy foam, the effects of various parameters including temperature, time profile and composition have to be characterized and optimized. This paper reports the use of the Taguchi method in characterizing and optimizing the sintering process parameters of titanium alloys. The effect of four sintering factors: composition, sintering temperature, heating rate and soaking time to the density has been studied. The titanium slurry was prepared by mixing titanium alloy powder, polyethylene glycol (PEG), methylcellulose and water. Polyurethane (PU) foam was then impregnated into the slurry and dried at room temperature. This was later sintered in a high temperature vacuum furnace. The various factors were assigned to an L9 orthogonal array. From the Analysis of Variance (ANOVA), the sintering temperature was found to give the highest percentage of contribution (34.73) followed by the composition of the titanium alloy powder (26.41) and the heating rate (0.64). The optimum density for the sintered titanium alloy foam was 1.4873Â±0.918 gcm-1. Confirmatory experiments have produced results that lay within the 90% confidence interval